Olualê Kossola e Zora N. Hurston: Notas sobre oralidade,imagem e etnografia - Batista, Nicole (2024)
The text aims to present an analysis of the images and ethnographic text produced in the late 1920s by anthropologist Zora Neale Hurston with Olualê Kossola, considered one of the last surviving African men of the illegal slave trade in the USA. The analysis covers Barracoon. The story of the last «Black Cargo» (2021), a text narrated in the first person based on oral transcripts, and the images filmed by this anthropologist in the same context. The notes presented in this article aim to address aspects of Hurston’s «griot anthropology» (Basques, 2021), her ethnographic method, shedding light on the ways in which the alliance between image, writing and orality comprise traits of the author's innovative methodology. Concluding on the relevance of her method's contribution to contemporary anthropology.